Normothermic Machine Perfusion vs. Static Cold Storage in Liver Transplantation: A Systematic Review and Meta‐Analysis - Viana, Patricia; Castillo‐Flores, Samy; Mora, Maria M. R.; Cabral, Thamiris D. D.; Martins, Paulo N.; Kueht, Michael; Faria, Isabella (Artificial organs, 2025)
ABSTRACT Background Normothermic machine perfusion (NMP) represents an alternative to prolong liver preservation and reduce organ discard rates. We performed an updated systematic review and meta‐analysis to compare NMP with static cold storage (SCS) in liver transplantation. Methods MEDLINE, Embase, and Cochrane were searched for randomized controlled trials (RCTs) or observational studies. Risk ratios (RR) and mean differences were calculated. p < 0.05 was considered significant. A random‐effects model was applied for all outcomes. PROSPERO ID: CRD42023486184. Results We included 1295 patients from 5 RCTs and 6 observational studies from 2016 to 2023. 592 (45.7%) underwent NMP. A subgroup RCT analysis favored NMP for non‐anastomotic strictures (RR 0.4; 95% CI 0.2, 0.9), postreperfusion syndrome (RR 0.4; 95% CI 0.27, 0.56), and early allograft dysfunction (RR 0.6; 95% CI 0.4, 0.9). NMP favored higher organ utilization rates (RR 1.1; 95% CI 1.02, 1.18). No significant differences between NMP and SCS were observed in graft survival or patient survival at 12 months, primary non‐function, serious adverse events, overall biliary complications, AST, or bilirubin levels peak within the first 7 days, ICU or hospital length of stay. Conclusion Our findings suggest that NMP is associated with lower non‐anastomotic biliary stricture rates, postreperfusion syndrome, early allograft dysfunction, and higher organ utilization in the RCT subgroup analysis, without increasing adverse events. Our findings suggest that NMP is associated with lower non‐anastomotic biliary stricture rates, postreperfusion syndrome, and early allograft dysfunction rates, without increasing adverse events or other biliary complications. These findings support a wider adoption of NMP as an alternative to increasing the donor pool in liver transplantation.